Exploration of facebook as a tool for improving marketing services at the University of Limpopo - Kaka, Khutloano Trudy (My University, 2022)
Social networking became a common international trend which has spreads and reached almost every corner of the world. The use of social media platform has developed and exploded into an online platform where individuals can generate content, share it, bookmark it and network at an enormous rate. Amongst the users of social media, students and youth are the main users of social media sites. The research explored Facebook as a tool for improving marketing services at University of Limpopo. Institution of higher learning utilise Facebook for various reasons such getting more followers, maintain existing relationship between the university and its audience and also to communicate with the university audience. Social media can have a great impact on the university and its audience depending on the usage as a two-way communication platform. The main objectives of the study are to identify the manner in which institutions of higher learning use Facebook for marking purposes; examine the performance of Facebook for marketing; and establish the challenges and opportunities of using Facebook as a marking tool. The study employed Nick Couldry’s practice theory and Marketing communication mix theory which are highlighting the relationship between the media, people and organisations. The study also analysed other literature that supports the aim and objectives of the study. A qualitative method was used in the study and results obtained through the use of online observation and semi-structured interview. Content and thematic analysis was applied to analyse the data collected. The population used as a sample were marketing and communication department employees at the University of Limpopo who are working with the university social media pages. With online observation of the University of Limpopo’s Facebook page the findings show that the university’s social media portray specifically Facebook as a one-way communication which they convey messages on the platform without taking into consideration the comments, criticism and queries of the students or audience at large. The empirical findings of the study indicate that Facebook is the most used social media platform at the University of Limpopo. Moreover, participants have highlighted that the purpose of all social media platforms are used to market the institution and as platforms to convey messages to their followers, staff members and university community. v The findings expose the various opportunities and challenges in using social media. However, it is proved that the opportunities outweigh the threats. Some institutions of higher learning use more than one social media platform. However, Facebook was proven to be the most widely used social media followed by YouTube, Twitter and Instagram.
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2022
Keywords: Facebook; Marketing; Institutions; University of Limpopo; Organisation; Social media; Audience; Facebook (Electronic resource); Social media; Online social networks; Social media -- Marketing